“Yes, but this Other One Looks Better/Works Better”: How do Consumers Respond to Trade-offs Between Sustainability and Other Valued Attributes? - Luchs, Michael G. (Journal of business ethics, 2017)
Consumers are increasingly facing product evaluation and choice situations that include information about product sustainability, i.e., information about a product’s relative environmental and social impact. In many cases, consumers have to make decisions that involve a trade-off between product sustainability and other valued product attributes. Similarly, product and marketing managers need to make decisions that reflect how consumers will respond to different trade-off scenarios. In the current research, we study consumer responses across two different possible trade-off scenarios: one in which consumers face a trade-off between product sustainability and hedonic value, and another in which they must trade-off between product sustainability and utilitarian value. Our results suggest that, overall, consumers are more likely to trade-off hedonic value (e.g., esthetics) for sustainability than to trade-off utilitarian value (e.g., functional performance) for sustainability. In Studies 1A and 1B, we presented participants with a product choice task and also measured their anticipatory emotions as they contemplated their options. The results suggest that given a trade-off, consumers are more likely to choose a sustainable product when they have to trade-off hedonic value than when they have to trade-off utilitarian value. Further, these studies provide some insight into the emotions underlying this effect. In Study 2, we use a different consumer response measure, relative purchase likelihood, and investigate the effect of trade-off type across categories that vary in the degree to which hedonic and utilitarian attributes are perceived to be important (referred to as ‘product type’). Our results suggest that the effect of trade-off type still holds, yet is moderated by product type such that consumers’ greater willingness to trade-off hedonic value (vs. utilitarian value) for sustainability is attenuated as the relative importance of hedonic (vs. utilitarian) attributes increases. In addition to building on our theoretical understanding of decision making given trade-offs with moral attributes, this research is also intended to support managers as they define and choose among various strategic, product development, and marketing promotion options.